New fatigue device for testing cables: Design and results. Issue 8 (29th April 2019) - Erena, Diego; Vázquez Valeo, Jesus; Navarro, Carlos; Domínguez, Jaime
Abstract: The fracture of cables is often caused by fatigue phenomena. To analyse the fatigue behaviour of these elements, a device has been designed, manufactured, and validated. This machine can produce different load states for the specimens, combining variable axial loads and variable bending moments. The testing machine has been designed to achieve two goals: to avoid the fracture of the cable in the vicinity of the clamps and to assure that the fracture of the cable is in the middle of the length of the specimen. The type of failure will be due to a combination of global stresses and fretting fatigue phenomena. This work also shows the results of different fatigue tests for a specific strand configuration. Finally, the fracture and contact surfaces of the strand have been analysed with a scanning electron microscope (SEM). The results obtained with this device show that it is adequate for testing cables and strands subjected to different combinations of axial loads and bending moments.